The Social Construction of Policy Targets and the Interest Groups - Luminița Gabriela POPESCU (Transylvanian Review of Administrative Sciences, 2007)
Frequently the major pressures on the political system are generated by groups that project their objectives and interventions – private interest groups. The presence of these groups in the public arena is considered destructive, and the influences they exercise on the political system are deemed similar to those of corruption. However, political analysts consider that, effects notwithstanding, the presence of interest groups represents an unavoidable cost in any democratic system. A reason for maintaining interest groups is the connection established between citizens and public officials through unions and business, trade or professional associations. The value of such a link may be equivalent to the actual price of the unavoidable distortion that occurs when interest groups are active within the public policy process. The interest groups are certainly too important to be eliminated under the pressure of the myth of corruption.